Faktor-Faktor Yang Berhubungan dengan Kepatuhan Ibu Hamil dalam Mengkonsumsi Tablet Fe - Suryana, Ella; Rahmawati, Eka; Arief, Ahmad (JURNAL KESEHATAN TERAPAN, 2025)
One of the government's efforts to prevent anemia in pregnant women is through a program providing iron tablets. This study aims to determine the relationship between knowledge, attitudes and family support simultaneously with pregnant women's compliance with consuming Fe tablets at the Palembang Campus Health Center. Analytical survey research method with a cross-sectional approach. The population in this study were all second and third trimester pregnant women in the Palembang campus health center work area in January-April 2024, namely 120 pregnant women. Samples were taken using accidental sampling technique with a total sample of 34 respondents, data analysis used univariate and bivariate analysis with the chi square statistical test. Univariate results showed that of the 34 respondents who complied with consuming Fe tablets, 22 respondents (64.3%) and 12 respondents who did not comply with consuming Fe tablets (35.5%). The results of bivariate analysis using the chi square test show that there is a relationship between knowledge (p value = 0.025), attitude (p value = 0.015) and family support (p value= 0.042) with the compliance of pregnant women with consuming Fe tablets at the Palembang Campus Health Center in 2024. It is hoped that The results of this research can be an illustration for the community health center to further increase the compliance of pregnant women with consuming Fe tablets by providing information to pregnant women about the benefits of Fe tablets.